2012
DOI: 10.3945/ajcn.111.024380
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research on the relation between food price changes and food-purchasing patterns: a targeted review

Abstract: One way in which to modify food purchases is to change prices through tax policy, subsidy policy, or both. We reviewed the growing body of experimental research conducted in the laboratory and in the field that investigates the following: the extent to which price changes influence purchases of targeted and nontargeted foods, total energy, or macronutrients purchased; the interaction of price changes with adjunctive interventions; and moderators of sensitivity to price changes. After a brief overview of econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
179
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(189 citation statements)
references
References 74 publications
2
179
0
1
Order By: Relevance
“…There is growing evidence suggesting that health-related food taxes and subsidies (e.g. a soft drink tax or a fruit and vegetable subsidy) are effective in improving population diets (35)(36)(37)(38)(39)(40) . Likewise, there is evidence that fiscal policy might not only work to improve the health profile of population diets, but also improve the environmental footprint (41) , showing the important link between agriculture, health and global greenhouse gas emissions (42) .…”
Section: Resultsmentioning
confidence: 99%
“…There is growing evidence suggesting that health-related food taxes and subsidies (e.g. a soft drink tax or a fruit and vegetable subsidy) are effective in improving population diets (35)(36)(37)(38)(39)(40) . Likewise, there is evidence that fiscal policy might not only work to improve the health profile of population diets, but also improve the environmental footprint (41) , showing the important link between agriculture, health and global greenhouse gas emissions (42) .…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that those with lower socioeconomic status have less access to fresh fruits and vegetables (21). Epstein et al (2012) showed that increased availability of healthier alternatives resulted in increased purchases of these foods (22). Moreover, Haire-Joshu et al (2004) found that exposure and preference for fruits and vegetables, trying new foods, and intake of fruits and vegetables in adulthood are considerably related to childhood dietary behavior (23).…”
Section: Discussionmentioning
confidence: 99%
“…These trials include for example the New Zealand SHOP study [47] and a recently published French study on the effects of fruit and vegetable vouchers [49]. All four studies focused on the effects of providing discounts on healthier foods and did not contain detailed data on substitution effects [48]. The main reason for the absence of large experimental trials on the effects of food pricing strategies is that those are complex, costly and sometimes even impossible to conduct in real-life.…”
Section: What Type Of Research Is Needed?mentioning
confidence: 99%
“…Moreover, the results of RCT's form an important input for the data used in simulation modelling studies. A recent review on experimental food pricing research has revealed that only four supermarket food pricing experiments have been published up to date [48]. These trials include for example the New Zealand SHOP study [47] and a recently published French study on the effects of fruit and vegetable vouchers [49].…”
Section: What Type Of Research Is Needed?mentioning
confidence: 99%